Exploring the Relationships Between Four Aging Ideals: A Bibliometric Study - Lin, Ka; Ning, Yumei; Mumtaz, Ayesha; Li, Hua (Frontiers in Public Health, 2022)
Examining the research articles on the Web of sciences, four ideas of successful aging, healthy aging, productive aging and active aging, are explored by conducting bibliometrics analyses. With the literature analysis from Web of sciences, the general information of four aging ideals were understood by visualization analysis, and the intellectual base and research hotspots were intuitively observed in the ﬁeld of four aging ideals. CiteSpace was used to identify the co-occurrence analysis of keywords to obtain the research trend and cutting-edge knowledge in the field of aging policies. Centrality analysis of keywords was conducted to know the pivotal or turning points among these four aging paradigms. Subsequently, the study reveals the nature of the relationship between these four aging ideals and disclose the links between their fundamental principles. It enhances understandings for diverse contexts of the ageing ideal facilitating ageing policies, which ground dissimilar strategies of development. The study extends the discussion about their relations with a conclusion on their policy implications. To identify new directions for ageing practices and provide innovative insights and references for investigators.